Perceptions of Husband/Wife Couples about Belis (In Terms of The Subjective Well-Being) - Vera Juliana Ribka Lango; Indra Yohanes Kiling; Yeni Damayanti (Journal of Health and Behavioral Science, 2022)
Perception is a sensing process where the stimulus is received by the individual through the senses and then interpreted so that the individual understands the stimulus he receives. A husband/wife pair is known as a man and a woman who are united in a legal marriage to form a happy and prosperous family both physically and mentally. Marriage of husband/wife couples in NTT cannot be separated from the customs known as "Belis". Belis or dowry is a gift from the groom to the woman in a large amount of value. Marriage by a husband/wife couple can be done using a belis or without a belis. Subjective well-being is when the individual assesses the quality of life as expected, so that pleasant and prosperous emotions arise. So this literature review discusses the perception of married couples using belis and without belis. Evidence shows that married couples using belis do not feel subjective well-being and husband/wife couples who marry without belis feel subjective well-being.